The Situation in Hungary. Special Report of the Special Committee on the Problem of Hungary. Plenary Meeting 785th, Thirteenth Session , Agenda Item 69 - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations. General Assembly Continuation of the previous document. Discusses the resolutions A3592 from June 1957 and A3849 from July 1958. These resolutions call for 1) the Soviet Union to desist from repressing the Hungarian people; 2) respect for fundamental human rights and freedoms 3) assurance of the liberty and political independence of the Hungarian people. The Soviet representative accuses the United States of intervening in Hungarian internal affairs.